Chronic vulvovaginal pruritus treated successfully with GnRH analogue - Banerjee, A K (BMJ Group, 2006)
A Medline search shows that this is the first reported case where vulvovaginal pruritus was treated successfully with a GnRH analogue. The report describes a patient with chronic premenstrual vulvovaginal pruritus thought to be attributable to autoimmune progesterone dermatitis.